ANALISIS PENERIMAAN DOSIS RADIASI DI ORGAN MATA PADA PEMERIKSAAN NASOFARING MENGGUNAKAN CT SCAN - Masdi Masdi; Evi Setiawati; Choirul Anam (Youngster Physics Journal, 2013)
ABSTRACTThe examination of nasopharynx CT Scan for the diagnosis tumors, was performed by two phase, plain phase and contrast medium phase, so will result in a very high radiation dose to the organs in the head especially the eyes. This study aimed to obtain the value of the radiation dose was received organ in the eye in patient who underwent nasopharynx CT Scan.  The study was begun by measuring the consistency of the output X-ray tube voltage (kVp Output). Furthermore, measurement of the radiation dose to the organ eye using TLD-100 chips were placed on the surface of the eye organ of the 22 different patients with sequences and spiral scan mode, and using the slice number between 24 to 39. Measurement technique was done by using a tube voltage and tube current time fixed at 130 kVp, 250 mAs, slice thickness and slice collimation of 4 mm and 6x2 mm.The result on the eye organ doses of nasopharynx CT Scan two phase with sequence mode to obtain eye organ dose value between 83.291 mGy to 101.571 mGy, whereas the spiral mode to obtain eye organ dose values varied between 89.536 mGy to 109.359 mGy, showing that the value of the eye organ dose spiral modes greater than mode sequence. The results also showed that the value of the eye organ dose received about one fifth of the value of the damage threshold of the eye lens dose of 500 mGy. Key words: Eye dose, CT Scan, thermoluminisence dosimeter (TLD)